Philippines Financial Sector Assessment Program : Retail Payments - Karpinski, Karol (World Bank, Washington, DC, 2021)
This technical note, prepared based on the financial sector assessment program (FSAP) mission to the Philippines, presents the overview of retail payments in the country and assesses its various aspects against relevant international standards and guidance. The assessment covers twelve thematic areas, which include: (1) public and private sector commitment; (2) legal and regulatory framework; (3) governance arrangements; (4) market competitiveness; (5) financial and information and communications technology (ICT) infrastructures; (6) risk management; (7) access points; (8) product design; (9) awareness and financial literacy; (10) leveraging large-volume recurrent payment streams; (11) payment systems oversight; and (12) cooperation and information sharing. This paper aims to present a succinct but comprehensive assessment of the most important aspects of the retail payments market in the Philippines. The scope of the assessment also includes an examination of the nascent fintech ecosystem, insofar as it relates to the provision of payment services or using retail payment services and accompanying infrastructure to build other value-added products.